Dealing with cholera: exclusively the domain of environmental health practitioners? - Cheryl S le Roux (AOSIS, 2004)
Cholera outbreaks have a profound impact on the health and well-being of communities. Opsomming Cholera het 'n diepgaande invloed op die gesondheid en algemene welsyn van gemeenskappe. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.